Abstract 12628: Effects of Temperature and Humidity on Cerebrovascular Disease Hospitalization in a Super-Aging Society - Yoshida, Toshiya; Doi, Shunichi; Yoneyama, Kihei; Kawagoe, Yasuhito; Nakai, Michikazu; Yoko, Sumita; Ishibashi, Yuki; Izumo, Masaki; Tanabe, Yasuhiro; Harada, Tomoo; Akashi, Yoshihiro J (Circulation, 2023)
Introduction: Cerebrovascular disease is known as one of the leading causes of death and disability in the elderly worldwide. Although weather was reported as predictor with cardiovascular disease, it was few evidence with cerebrovascular disease in Japan. Hypothesis: The weather is correlate with cerebrovascular disease hospitalizations. Methods: The Japanese registry of all cardiac and vascular diseases database includes patients with cardio-cerebrovascular disease who required hospitalization and constitutes a nationwide dataset in Japan. This study included 4,998,541 consecutive patients with cardio-cerebrovascular disease requiring hospitalization were admitted between 2015 and 2019. We investigated the relationship between cerebrovascular disease hospitalization and temperature, or humidity. Results: Data were collected from 606,807consecutive patients with cerebrovascular disease admitted. In this study population, the median age was 75.0 (66.0-83.0) years and 55.8% of subjects were male. The mean weather temperature and humidity 1 day before cerebrovascular disease hospitalization were 17.2 °C and 69%, respectively. Multilevel mixed-effects linear regression models showed the association of temperature and humidity with cerebrovascular disease hospitalizations after adjusting for air pollution, hospital, and patient demographics. Lower mean temperatures and humidity <70% or humidity ≧70% are associated with an increased incidence of cerebrovascular disease hospitalization (coefficient, -1.442 [-1.473 to -1.411] per °C, p<0.001, coefficient, -0.084 [-0.112 to -0.056] per%, p < 0.001, and coefficient, 0.136 [0.103 to 0.168] per %, p < 0.001, respectively). Conclusions: Lower mean temperatures and extremely lower or higher humidity are both associated with an increased incidence of cerebrovascular disease hospitalization in the aging society of Japan.